Business Impact Analysis Untuk Penanganan Gangguan Bisnis di Lembaga Perbankan - M Hadi Prayitno; Hendarman Lubis (STMIK Budi Darma, 2019)
Banks are financial institutions that have a very large influence on the economic system in business processes and individuals. Our lives seem to be inseparable from the services offered by banks. Paying attention to this makes the regulator must be able to regulate its banking interests and customers. In this study, Banking institution has identified various kinds of impacts that can be disruptive, in its business process. In addition, the maximum tolerance period (MLTD) has also been determined for recovery, which can cause disruption to the business. With the Business Impact Analysis, Banking institution knows the maximum time tolerated before being recovered, and knows its financial and non financial impacts, which in the end Banking institution can make decisions when a business has a business interruption, thereby minimizing the losses that might be caused.